Pengembangan Media Powerpoint Interaktif Berbasis Kearifan Lokal Pada Pembelajaran IPA SDN 14 Mendo Barat - Yurdayanti Yurdayanti; Nuraini Nuraini; Afriyani Afriyani; Ayu Pradina; Dea Angelica; Dea Gustiani; Elisa Amanda; Nia Nopita Sari; Offie Indah Resta; Umi Kalsum; Zhien Zha Oetami (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
The purpose of this study was to determine the procedure for developing research and to determine the quality of the feasibility of interactive powerpoint-based learning media in science subjects for the Parts and Functions of Local Plants Typical of Bangka Belitung. This research is a development research (R&D) which refers to the ADDIE development model which includes five steps, namely analysis, design, development, implementation, and evaluation. Data collection techniques in this study used interview techniques, documentation and questionnaire sheets. Data analysis techniques used in assessing product feasibility by experts, teachers, and students in this development research used a Likert scale. Based on the research results, it is known that the validation results of material experts show an average percentage of 87.5% with valid information (very suitable for use), media experts get an average percentage of 88.75% with valid information (very suitable for use), linguists get the average percentage is 80% with valid information (very feasible to use). The assessment of product feasibility by the teacher gets an average percentage of 96% with valid information (very suitable for use), and students get an average percentage of 80% with valid information (very suitable for use). The overall average score is 88.07%, indicating that the interactive powerpoint-based learning media developed by the researcher is suitable to be used as a learning tool or media for teachers and students.